2016
DOI: 10.1089/ten.tea.2015.0277
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cell-Seeded Hydrogels Increase Endogenous Progenitor Cell Recruitment and Neovascularization in Wounds

Abstract: Adipose-derived mesenchymal stem cells (ASCs) are appealing for cell-based wound therapies because of their accessibility and ease of harvest, but their utility is limited by poor cell survival within the harsh wound microenvironment. In prior work, our laboratory has demonstrated that seeding ASCs within a soft pullulancollagen hydrogel enhances ASC survival and improves wound healing. To more fully understand the mechanism of this therapy, we examined whether ASC-seeded hydrogels were able to modulate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 39 publications
2
37
0
1
Order By: Relevance
“…Previous studies have shown the ability of ADSCs to enhance wound healing when seeded into hydrogels, with increased angiogenesis and proliferation compared with nonseeded scaffolds. 18 , 19 Our histologic and immunohistochemical analyses of cHG show similar results. cHG-treated wounds had significantly decreased wound length, increased collagen production, enhanced angiogenesis, and accelerated cell proliferation compared with control.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown the ability of ADSCs to enhance wound healing when seeded into hydrogels, with increased angiogenesis and proliferation compared with nonseeded scaffolds. 18 , 19 Our histologic and immunohistochemical analyses of cHG show similar results. cHG-treated wounds had significantly decreased wound length, increased collagen production, enhanced angiogenesis, and accelerated cell proliferation compared with control.…”
Section: Discussionsupporting
confidence: 78%
“…ASCs have outstanding self-renewal potential, paracrine function, and the capacity to differentiate into multiple phenotypes. Some data have suggested the application of ASCs in lesions induces healing because of the role of ASCs in stimulating angiogenesis, which is attributed to their endothelial differentiation and release of several cytokines under specific conditions [21-24]. …”
Section: Discussionmentioning
confidence: 99%
“…Use of topical stem cell therapies that can release growth factors and modulate macrophage responses is one strategy 98 . In addition to modulating the immune response, stem cell-based therapies are associated with a myriad of benefits including improvement of neovascularization by influencing endothelial cells, promoting ECM deposition by influencing fibroblasts and increasing recruitment of progenitor cells into wounds 99,100 .…”
Section: Macrophages In Chronic Woundsmentioning
confidence: 99%